Study on Field Test and Seismic Performance of MJS Joint Microdisturbance Reinforcement on Existing Tunnel - Zhanyou Luo; Yongheng Deng; Baoping Zou; Jianfeng Zhu; Mingyao Jiang; Kuangqin Xie (Shock and Vibration)
Metro Jet System (MJS) joint microdisturbance reinforcement is often adopted to strengthen and remediate existing tunnels that are severely deformed by under-construction peripheral works, but analysis related to the reinforcement system of tunnel under consideration of seismic effects is insufficient at present. In this work, a field test of MJS joint microdisturbance reinforcement system of existing tunnels was conducted on the basis of a subway tunnel deformation reinforcement project. Then, a numerical simulation study of the seismic dynamic response of reinforcement system was performed in combination with seismic wave direction and intensity. Results show that the MJS joint microdisturbance reinforcement measures can effectively reduce the settlement and horizontal radial convergence deformation of the tunnel. The seismic longitudinal wave significantly affects the vertical displacement of the tunnel, and the seismic-induced vertical displacement of the tunnel increases with the rise in seismic intensity. The seismic transverse wave significantly affects the horizontal radial convergence deformation of the tunnel, and the seismic-induced horizontal radial convergence deformation of the tunnel increases with the rise in seismic intensity. The antiseismic property of MJS joint microdisturbance reinforcement measures on the existing tunnel is not obvious.